The Apartment Complex : Urban Living and Global Screen Cultures - Wojcik, Pamela Robertson, 1964- (Book collections on Project MUSE., 2018)
From the bachelor pad that Jack Lemmon's C.C. Baxter loans out to his superiors in Billy Wilder's "The Apartment" (1960) to the crumbling tenement in a dystopian Taipei in Tsai Ming-liang's "The Hole" (1998), the apartment in films and television series is often more than just a setting: it can motivate or shape the narrative in key ways. Such works belong to a critical genre identified by the author as the apartment plot, which comprises specific thematic, visual, and narrative conventions that explore modern urbanism's various forms and possibilities. In this book a diverse group of international scholars discuss the apartment plot in a global context, examining films made both within and beyond the Hollywood studios. The contributors consider the apartment plot's intersections with film noir, horror, comedy, and the musical, addressing how different national or historical contexts modify the apartment plot and how the genre's framework allows us to rethink the work of auteurs and identify productive connections and tensions between otherwise disparate texts.